Reassessing Joseph Smith Jr.'s Formal Education - Davis, William (2016)
The article discusses the formal education of Joseph Smith, American religious leader and founder of Mormonism and the Latter Day Saint movement. It mentions assumptions about his formal education or lack thereof, and how both detractors and supports use Smith's lack of formal education to strengthen their views. The article includes a review of Smith's common school education, and a survey of his educational experiences.
Keywords: Church of Jesus Christ of Latter-day Saints; Education; Mormon Church -- History -- 19th century; Religious leaders; Smith, Joseph, 1805-1844